The Avocado Botany, Production and Uses (2nd Edition) - Schaffer, Bruce (CABI, 2014)
Information on the biology, production and utilization of avocado has been readily accessible for over 100 years in the form of articles in scientific and popular journals, advisory pam- phlets, bulletins, reports and booklets. These publications generally address aspects of crop botany, orchard management, and postharvest handling, and are usually specific to particular regions or countries. The need for a detailed, comprehensive scientific text, international in scope and summarizing our current knowledge of this fruit crop, was finally satisfied by the appearance of the first edition of this book in 2002, edited by A.W. Whiley, B. Schaffer and B.N. Wolstenholme. Global sharing of information on avocado was advanced by the First World Avocado Congress held in Pretoria, South Africa in 1987. This has been followed by regular congresses every 4 years in cities in different avocado-producing countries, including Orange, California, USA (1991); Tel Aviv, Israel (1995); Uruapan, Mexico (1999); Malaga, Spain (2003); Viña del Mar, Chile (2007); and most recently Cairns, Australia (2011), with the 8th Congress to be held in Peru in 2015. Proceedings of these congresses provide a rich source of scientific and marketing literature. Producers, scientists researching avocado, academics and extension advisers, marketers and serv- ice industry personnel have a regular opportunity to network and discuss major problems limiting production and marketing. A remarkable collegiality has developed over the years, which has encouraged the sharing of information, and considerable international cooperation in research and marketing. The Hofshi Foundation provides the Internet website Avocadosource.com, regu- larly updated in all matters relating to avocado literature, personalities and developments. The regular world avocado congresses, plus several annual or biennial national avocado congresses, research symposia, etc. in various avocado-producing countries have provided much of the sci- entific literature summarized in this book. They also helped bridge the divide between English- and Spanish-speaking countries, the latter providing most of the commercial crop and undergoing the most rapid growth.